First report of paternal uniparental disomy of chromosome 8 with SLC52A2 mutation in Brown-vialetto-van laere syndrome type 2 and an analysis of genotype-phenotype correlations - Zhao, Siyu; Che, Fengyu; Yang, Le; Zheng, Yanyan; Wang, Dong; Yang, Ying; Wang, Yan (Frontiers in Genetics, 2022)
Abstract Purpose: This study reports the clinical and genetic features of Brown-Vialetto-Van Laere syndrome (BVVLS) in a case of uniparental disomy of chromosome 8 in mainland China and analyzes the genotype-phenotype correlation through a review of the literature. Methods: The clinical characteristics, treatment, and follow-up data of the patient were summarized, and the etiology was identified by whole-exome sequencing and gene chip analysis. Correlations between the genotype and phenotype were analyzed by collecting clinical and genetic data of published cases and our patient . Results: We identified a homozygous mutation in SLC52A2 (NM_001253815.2 c.1255G>A) by trio-WES. Sanger sequencing confirmed that his father was heterozygous and his mother was normal. Subsequently, paternal uniparental disomy of chromosome 8[UPD(8)pat] was confirmed by chromosomal microarray analysis.The patient received long-term oral riboflavin treatment (7 mg/kg.d) and was followed up for 40 months by which time the child's bulbar palsy, ataxia, and motor function had improved. A review of the literature and statistical analysis found that the symptoms of BVVLS appear at the earliest shortly after birth and at the latest at 10 years of age. The median age of onset was 2.5 years, but the overall delay in diagnosis was a median of 5.6 years. The most common symptoms were hearing loss (83.9%), followed by muscle weakness (80.6%), visual impairment (64.5%), and ataxia (61.3%). To date, a total of 32 mutations in the SLC52A2 gene have been reported, with the most common being a missense mutation. In patients with missense mutations, homozygous pattern was more likely to present with ataxia as the first symptom(P<0.05), while compound heterozygous pattern was more likely to develop respiratory insufficiency during the course of disease(P<0.001). Moreover, patients with one missense mutation located in inside the transmembrane domain were more likely to have respiratory insufficiency than those with mutations both inside and outside the domain (P<0.05). Riboflavin supplementation was an important factor in determining prognosis (P<0.001). Conclusion: We report the first UPD(8)pat with SLC52A2 homozygous pathogenic mutation case in BVVLS, which expand the mutation spectrum of gene.